Magnetic particle-protein fiber 3D stent and preparation method and application thereof
Through the design of magnetic particles-protein fiber 3D scaffolds, combined with 3D printing technology and protein self-assembly, the problems of traditional bone repair materials in terms of biocompatibility and mechanical properties balance are solved, and effective adhesion, proliferation and differentiation of bone cells are achieved. , promotes bone regeneration.
Patent Information
- Application Number
- CN202411397185.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
Existing bone repair materials have problems such as disease, immune and inflammatory response at the donor site, and traditional 3D scaffolds are difficult to balance biocompatibility and mechanical properties, limiting the adhesion, proliferation and differentiation of bone cells.
Using magnetic particles-protein fiber 3D scaffolds, polylactic acid, glycolide, paraoxycyclohexanone and grafted hydroxyapatite are used as main raw materials, and porous scaffolds are constructed in combination with 3D printing technology, and protein and negatively charged silicon oxide magnetic beads are used. The self-assembly of the magnetic particle-protein fiber layer forms a magnetic particle-protein fiber layer, simulates the natural extracellular matrix structure, and improves biocompatibility and mechanical strength.
A 3D scaffold with excellent biocompatibility and good mechanical strength of magnetic particles-protein fibers is achieved, which promotes the adhesion, proliferation and differentiation of bone cells, accelerates bone regeneration, and solves the shortcomings of traditional scaffolds in the balance of mechanical properties and biocompatibility. .
Smart Images

Figure CN119280471A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical engineering technology, and in particular to a magnetic particle-protein fiber 3D scaffold and a preparation method and application thereof. Background Art
[0002] Large-scale bone damage caused by various reasons is difficult to self-repair, and bone repair materials are a practical way to solve the problem of bone defect repair. In recent years, bone repair materials have developed rapidly, from autologous bone, allogeneic bone, inert materials, etc. to highly active and multifunctional bone tissue engineering scaffold materials. Although bone repair materials have developed rapidly, there are still problems such as donor site morbidity, immunity and inflammatory response. In the field of tissue engineering, 3D scaffolds play a key role as cell culture matrices in the repair of tissues such as bone and cartilage. People are paying more and more attention to how to design 3D scaffold materials with good biocompatibility and degradability to promote the effective repair of bone tissue. The ideal 3D scaffold needs to have a specific porosity, pore size, certain osteoconductivity, etc. to promote cell adhesion, proliferation and differentiation.
[0003] Traditional 3D scaffolds often use direct protein modification methods for surface treatment. For example, polylactic acid is used as a raw material combined with 3D printing technology to construct a polylactic acid scaffold, and then the scaffold surface is modified by collagen coating. In in vitro experiments, obvious new bone mineralization process can be seen (Q. Wang, YB Feng, M. He, WF Zhao, L. Qiu, CS Zhao, A Hierarchical Janus Nanofibrous Membrane Combining Direct Osteogenesis and Osteoimmunomodulatory Functions for Advanced Bone Regeneration, Adv Funct Mater. 31 (8) (2021). However, due to the weak adsorption capacity of proteins and the fact that they only improve one feature of the cell membrane, their biological effects are often limited, and it is difficult to balance the biocompatibility and mechanical properties of the scaffold. Summary of the invention
[0004] In view of this, the present invention provides a magnetic particle-protein fiber 3D scaffold and its preparation method and application. The 3D scaffold provided by the present invention has excellent biocompatibility and good mechanical strength. It can also simulate the fiber structure of natural extracellular matrix, promote the adhesion, proliferation and differentiation of bone cells, and has broad application prospects in the fields of bone defect repair.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for preparing a magnetic particle-protein fiber 3D scaffold comprises the following steps:
[0007] The polylactic acid, glycolide, cyclohexanone, a catalyst and a solvent are mixed to carry out a polymerization reaction to obtain a copolymer;
[0008] The copolymer and grafted hydroxyapatite are mixed to obtain a copolymer-grafted hydroxyapatite composite; the grafted hydroxyapatite comprises hydroxyapatite and a silane coupling agent grafted on the surface of the hydroxyapatite;
[0009] 3D printing the copolymer-grafted hydroxyapatite composite to obtain a porous 3D scaffold;
[0010] The magnetic protein solution is dripped onto the porous 3D scaffold for self-assembly to obtain the magnetic particle-protein fiber 3D scaffold; the magnetic protein solution includes a protein solution and negatively charged silica magnetic beads dispersed in the protein solution; the negatively charged silica magnetic beads include Fe3O4 nanoparticles, a silica layer coated on the surface of the Fe3O4 nanoparticles, and a carboxyl functional group modified on the silica layer.
[0011] Preferably, the mass ratio of the polylactic acid, glycolide and cyclohexanone is 50-90:5-25:5-25;
[0012] The weight average molecular weight of the polylactic acid is 50,000 to 150,000;
[0013] The catalyst comprises one or more of organic tin and organic sulfonic acid; the mass of the catalyst is 0.05-5% of the total mass of the polylactic acid, glycolide and cyclohexanone.
[0014] Preferably, the polymerization reaction temperature is 130-145° C., and the reaction time is 70-84 h.
[0015] Preferably, the preparation method of the grafted hydroxyapatite comprises: mixing hydroxyapatite, a silane coupling agent and an alcohol solvent for grafting reaction to obtain the grafted hydroxyapatite; the grafting reaction temperature is 120 to 140° C., and the reaction time is 5 to 7 hours.
[0016] Preferably, the silane coupling agent includes one or more of γ-methyl methacrylate silane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and 3-aminopropyltriethoxysilane;
[0017] The molar ratio of the hydroxyl groups on the surface of the hydroxyapatite to the alkoxy groups in the silane coupling agent is 1:1-2.
[0018] Preferably, the method of mixing the copolymer and the grafted hydroxyapatite comprises: dissolving the copolymer in an organic solvent to obtain a copolymer solution; mixing the grafted hydroxyapatite and the copolymer solution, and drying the obtained mixed liquid to obtain the copolymer-grafted hydroxyapatite composite;
[0019] The mass ratio of the copolymer to the grafted hydroxyapatite is 7-9:1-3.
[0020] Preferably, the 3D printing conditions include: a printing temperature of 180-220° C., a layer thickness of 0.1-0.3 mm, a printing speed of 20-60 mm / s, a filling density of 20-80%, and a linear or mesh printing path;
[0021] The porous 3D scaffold has a porosity of 60-90% and a pore size of 100-500 μm.
[0022] Preferably, the self-assembly is performed under magnetic field induction conditions, and the magnetic field intensity of the magnetic field induction is 0.1-0.5T.
[0023] The present invention also provides a magnetic particle-protein fiber 3D scaffold prepared by the preparation method described in the above scheme, comprising a porous 3D scaffold and a magnetic particle-protein fiber layer attached to the surface of the porous 3D scaffold, wherein the magnetic particle-protein fiber layer is formed by self-assembly of negatively charged oxidized magnetic beads and proteins.
[0024] The present invention also provides the use of the magnetic particle-protein fiber 3D scaffold described in the above scheme in the preparation of bone repair materials.
[0025] The invention provides a method for preparing a magnetic particle-protein fiber 3D scaffold, comprising the following steps: mixing polylactic acid, glycolide, cyclohexanone, a catalyst and a solvent for polymerization reaction to obtain a copolymer (PLPG); mixing the copolymer and grafted hydroxyapatite to obtain a copolymer-grafted hydroxyapatite composite; the grafted hydroxyapatite comprises hydroxyapatite and a silane coupling agent grafted on the surface of the hydroxyapatite; 3D printing the copolymer-grafted hydroxyapatite composite to obtain a porous 3D scaffold; dripping a magnetic protein solution on the porous 3D scaffold for self-assembly to obtain the magnetic particle-protein fiber 3D scaffold; the magnetic protein solution comprises a protein solution and negatively charged silica magnetic beads dispersed in the protein solution; the negatively charged silica magnetic beads comprise Fe3O4 nanoparticles, a silica layer coated on the surface of the Fe3O4 nanoparticles, and a carboxyl functionalized group modified on the silica layer. The magnetic particle-protein fiber 3D scaffold provided by the present invention has a scaffold body with polylactic acid (PLLA), glycolide (GA), cyclohexanone (PDO) and hydroxyapatite (HA) as main raw materials. The introduction of GA and PDO units can effectively improve the mechanical properties of the polylactic acid scaffold and adjust the degradation performance. In addition, the present invention adopts a silane coupling agent to graft and modify the hydroxyapatite, which not only makes the hydroxyapatite evenly distributed in the PLPG scaffold, but also improves the compressive strength and cell affinity of the scaffold, and finally obtains a scaffold structure with excellent biocompatibility and good mechanical strength.
[0026] In addition, the present invention uses protein and negatively charged oxidized magnetic beads for self-assembly to form magnetic particle-protein fibers on the surface of the porous 3D scaffold. The magnetic particle-protein fiber assembly contains magnetic particles, which can simulate the bioelectric signals of the bone itself, improve the bone conductivity and bone induction activity of the material, promote bone cell activity and bone regeneration, and enhance protein adsorption, guide and regulate cell behavior, promote bone cell adhesion, proliferation and differentiation, and accelerate vascularization and bone regeneration.
[0027] In summary, the present invention uses polylactic acid, glycolide, cyclohexanone and grafted hydroxyapatite as main raw materials, combines 3D printing technology to construct a scaffold, and modifies the scaffold by autonomously installing proteins and negatively charged oxidized magnetic beads on the surface of the scaffold. It combines the advantages of nano-composite porous scaffolds and nano-composite fiber scaffolds to prepare a new type of composite 3D scaffold, which has a specific porosity and crystallinity, the same supporting force as the main bone, and can simulate the fibrous structure of the natural extracellular matrix, which is beneficial to the in vitro regulation of cell adhesion, migration and proliferation behavior, and has broad application prospects in the fields of bone defect repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a picture of the porous 3D scaffold prepared in Example 1;
[0029] Figure 2 This is a microscope image of a 2D planar biomimetic static fiber layer formed by self-assembly of different protein solutions and negatively charged silicon oxide magnetic beads in Example 2;
[0030] Figure 3 Microscope images of 2D planar bionic static fiber layers formed by magnetic protein solutions of different volumes in Example 2;
[0031] Figure 4 The results of the cell activity test of MC3T3-E1 cells in different magnetic particle-protein fiber assemblies in Example 3;
[0032] Figure 5 The live and dead cell staining results of MC3T3-E1 cells cultured on the porous 3D scaffolds before and after modification in Example 3 after 48 hours;
[0033] Figure 6 The immunofluorescence staining results and semi-quantitative analysis results of MC3T3-E1 cells cultured in a 2D planar bionic static fiber layer for 48 hours in Example 4;
[0034] Figure 7 The immunofluorescence staining results of MC3T3-E1 cells cultured on the porous 3D scaffolds before and after modification for 48 hours in Example 4;
[0035] Figure 8 The live and dead cell staining results of MC3T3-E1 cells in Example 5 after being cultured on the low-density coated scaffold for 48 hours. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing a magnetic particle-protein fiber 3D scaffold, comprising the following steps:
[0037] The polylactic acid, glycolide, cyclohexanone, a catalyst and a solvent are mixed to carry out a polymerization reaction to obtain a copolymer;
[0038] The copolymer and grafted hydroxyapatite are mixed to obtain a copolymer-grafted hydroxyapatite composite; the grafted hydroxyapatite comprises hydroxyapatite and a silane coupling agent grafted on the surface of the hydroxyapatite;
[0039] 3D printing the copolymer-grafted hydroxyapatite composite to obtain a porous 3D scaffold;
[0040] The magnetic protein solution is dripped onto the porous 3D scaffold for self-assembly to obtain the magnetic particle-protein fiber 3D scaffold; the magnetic protein solution includes a protein solution and negatively charged silica magnetic beads dispersed in the protein solution; the negatively charged silica magnetic beads include Fe3O4 nanoparticles, a silica layer coated on the surface of the Fe3O4 nanoparticles, and a carboxyl functional group modified on the silica layer.
[0041] The present invention mixes polylactic acid, glycolide, cyclohexanone, a catalyst and a solvent for polymerization reaction to obtain a copolymer (PLPG). In the present invention, the weight average molecular weight of the polylactic acid is preferably 50,000 to 150,000, and more preferably 80,000 to 120,000; the polylactic acid in the present invention is all left-handed polylactic acid (PLLA), which will not be repeated later; the mass ratio of the polylactic acid, glycolide and cyclohexanone is preferably 50 to 90:5 to 25:5 to 25, and more preferably 70 to 90:5 to 15:5 to 15. In a specific embodiment of the present invention, the mass ratio of the polylactic acid, glycolide and cyclohexanone is 90:5:5. Polylactic acid has poor brittleness and is difficult to provide long-term stable support for new bone tissue. The present invention can improve the biocompatibility of the polylactic acid scaffold, improve the material properties of the scaffold, and adjust the degradation rate of the polylactic acid by introducing cyclohexanone (PDO) and glycolide (GA).
[0042] In the present invention, the catalyst preferably includes one or more of organic tin and organic sulfonic acid, and the organic tin catalyst preferably includes one or more of stannous octoate (Sn(Oct)2), dibutyltin diacetate (DBT), tetramethyltin hydride (TMHT) and tetrabutyltin oxide (TBTO); the organic sulfonic acid catalyst is preferably p-toluenesulfonic acid (PTSA); the mass of the catalyst is preferably 0.05-5% of the total mass of the polylactic acid, glycolide and cyclohexanone; the solvent is preferably a halogenated alkane, more preferably dichloromethane; the present invention has no special requirements on the amount of the solvent, as long as it can make the polymerization reaction proceed smoothly.
[0043] In the present invention, the polymerization temperature is preferably 130-145°C, more preferably 135-140°C, and the polymerization time is preferably 70-84h, more preferably 72-80h. After the polymerization is completed, the present invention preferably further comprises: washing the obtained product liquid with a solvent, filtering and drying to obtain a copolymer powder.
[0044] After obtaining the copolymer, the present invention mixes the copolymer and grafted hydroxyapatite to obtain a copolymer-grafted hydroxyapatite composite; the grafted hydroxyapatite includes hydroxyapatite and a silane coupling agent grafted on the surface of the hydroxyapatite.
[0045] In the present invention, the preparation method of the grafted hydroxyapatite preferably comprises: mixing hydroxyapatite, a silane coupling agent and an alcohol solvent for grafting reaction to obtain the grafted hydroxyapatite; the temperature of the grafting reaction is preferably 120-140°C, the reaction time is preferably 5-7h, more preferably 6h, and the grafting reaction is preferably carried out under nitrogen protection; the hydroxyapatite is preferably nano-hydroxyapatite powder; the silane coupling agent preferably includes one or more of γ-methyl methacrylate silane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-isocyanate propyl triethoxysilane and 3-aminopropyl triethoxysilane; the molar ratio of the hydroxyl group on the surface of the hydroxyapatite to the alkoxy group in the silane coupling agent is preferably 1:1-2; the alcohol solvent is preferably ethanol. In a specific embodiment of the present invention, it is preferred to first add the hydroxyapatite to ethanol, ultrasonically disperse the hydroxyapatite uniformly, and then add the silane coupling agent.
[0046] After the grafting reaction is completed, the present invention preferably cools the reaction system to room temperature, and then sequentially performs ethanol washing, deionized water washing, centrifugation and freeze drying to obtain the grafted hydroxyapatite.
[0047] In the present invention, the method for mixing the copolymer and the grafted hydroxyapatite preferably includes: dissolving the copolymer in an organic solvent to obtain a copolymer solution; mixing the grafted hydroxyapatite and the copolymer solution, and drying the resulting mixed liquid to obtain the copolymer-grafted hydroxyapatite composite; the mass ratio of the copolymer and the grafted hydroxyapatite is preferably 7-9:1-3, specifically 7:3, 8:2 or 9:1; the organic solvent is preferably a halogenated alkane, more preferably dichloromethane; the amount ratio of the copolymer and dichloromethane is preferably 17-18g:100mL. In a specific embodiment of the present invention, it is preferred to first place the copolymer in a container, then add dichloromethane, stir until the copolymer is completely dissolved, then add the grafted hydroxyapatite, continue stirring to make the grafted hydroxyapatite uniformly dispersed in the copolymer solution, and then dry; the drying is preferably vacuum drying; the drying temperature is preferably 60°C, and the drying time is based on drying to constant weight.
[0048] The addition of hydroxyapatite can improve the mechanical strength of the stent, and hydroxyapatite is a kind of alkaline substance that can neutralize the acidic products of polylactic acid degradation, regulate the degradation rate, and alleviate the acidified local microenvironment; however, the interface compatibility between hydroxyapatite and polylactic acid is poor, which easily leads to agglomeration. The present invention modifies hydroxyapatite by grafting, so that hydroxyapatite can be evenly distributed in the stent, and a composite stent with higher mechanical strength can be prepared.
[0049] After obtaining the copolymer-grafted hydroxyapatite composite, the present invention performs 3D printing on the copolymer-grafted hydroxyapatite composite to obtain a porous 3D scaffold. In the present invention, the conditions of the 3D printing preferably include: a printing temperature of 180 to 220°C, preferably 200 to 210°C, a layer thickness of 0.1 to 0.3 mm, preferably 0.2 to 0.25 mm, a printing speed of 20 to 60 mm / s, preferably 30 to 50 mm / s, a filling density of 20 to 80%, preferably 40 to 70%, and a printing path preferably linear or mesh. In a specific embodiment of the present invention, the fiber diameter of the porous 3D scaffold obtained by printing is 300 μm, the fiber spacing is 300 μm, and the interlayer poor orientation is 90°; after printing, the obtained porous 3D scaffold is preferably freeze-dried and sterilized; the sterilization treatment is preferably carried out using 60Co-γ rays, and the irradiation dose is preferably 25 kGy.
[0050] In the present invention, the porosity of the porous 3D scaffold is preferably 60-90%, more preferably 70-80%, and the pore size is preferably 100-500 μm, more preferably 200-400 μm.
[0051] After obtaining the porous 3D scaffold, the present invention drips a magnetic protein solution onto the porous 3D scaffold for self-assembly to obtain the magnetic particle-protein fiber 3D scaffold; the magnetic protein solution includes a protein solution and negatively charged silica magnetic beads dispersed in the protein solution; the negatively charged silica magnetic beads include Fe3O4 nanoparticles, a silica layer coated on the surface of the Fe3O4 nanoparticles, and a carboxyl functionalized group modified on the silica layer.
[0052] In the present invention, when preparing the negatively charged oxidized magnetic beads, it is preferred to use a sol-gel method to coat silica on the surface of Fe3O4 nanoparticles to obtain silica-coated magnetic particles (denoted as Fe3O4@SiO2), and then the silica-coated magnetic particles are carboxyl functionalized to obtain the negatively charged oxidized magnetic beads; the reagent used for the carboxyl functional modification is preferably 3-methylacrylic acid (MAA).
[0053] The present invention has no special requirements on the specific preparation method of the Fe3O4 nanoparticles, and a method familiar to those skilled in the art can be used. In a specific embodiment of the present invention, a hydrothermal synthesis one-pot method is preferably used for preparation.
[0054] In a specific embodiment of the present invention, the sol-gel method for preparing silica-coated magnetic particles preferably includes the following steps: adjusting the pH value of the ethanol-deionized water mixture to 9.5-10.5 using ammonium hydroxide, then adding Fe3O4 nanoparticles under ultrasonic conditions, and then dropping a silicon source solution. After the dropwise addition is completed, stirring the reaction at room temperature for 12 hours, washing the resulting product to obtain silica-coated magnetic particles; the silicon source solution is preferably obtained by dissolving tetraethyl orthosilicate (TEOS) in ethanol, and the dosage ratio of the Fe3O4 nanoparticles and tetraethyl orthosilicate is preferably 150 mg:80 μL.
[0055] In a specific embodiment of the present invention, the method for functionalizing silica-coated magnetic particles with carboxyl groups preferably comprises: ultrasonically dispersing the silica-coated magnetic particles in anhydrous ethanol, then adding 3-methacrylic acid for condensation reaction, washing, centrifuging and vacuum drying the resulting reaction solution to obtain the negatively charged oxidized magnetic beads; the mass ratio of the silica-coated magnetic particles to 3-methacrylic acid is preferably 1:2-5, specifically 1:2, 1:3 or 1:5; the temperature of the condensation reaction is preferably 80-90°C, and the time is preferably 2-4h; the temperature of the vacuum drying is preferably 60-80°C, and the time is preferably 2-4h. The present invention can improve the dispersibility of magnetic nanoparticles and give them a negatively charged functionalized surface through carboxyl functionalization modification.
[0056] In the present invention, the protein in the protein solution is preferably one or more of fibronectin (Fn), laminin, type I collagen (COL-1), bovine serum albumin (BSA) and bovine fibrinogen (Fg); in a specific embodiment of the present invention, the corresponding protein can be selected according to the specific purpose, so as to realize the functionalization and personalization of bone repair materials, and provide a new solution for the application of 3D scaffolds in the field of tissue engineering; the solvent of the protein solution is preferably PBS, and the concentration of the protein solution is preferably 0.005-1 mg / mL; the present invention has no special requirements for the preparation method of the protein solution, and the method well known to those skilled in the art can be adopted.
[0057] In the present invention, the dosage ratio of protein to negatively charged oxidized magnetic beads in the magnetic protein solution is preferably 1-2 mL: 0.1-0.2 mg.
[0058] In the present invention, the preparation method of the magnetic protein solution preferably includes: ultrasonically dispersing the negatively charged oxidized magnetic beads in double distilled water to obtain a negatively charged oxidized magnetic bead dispersion, mixing the protein solution and the negatively charged oxidized magnetic bead dispersion for incubation, performing magnetic absorption treatment after forming clusters, and then blowing and resuspending. In the present invention, the incubation temperature is preferably 3 to 5°C, more preferably 4°C, the incubation time is preferably 10 to 20 minutes, and during the incubation period, it is preferably gently inverted up and down every 2 minutes; the magnetic absorption treatment time is preferably 2 to 10 minutes. In a specific embodiment of the present invention, the centrifuge tube is preferably placed on a magnetic stand for magnetic absorption; the blowing and resuspending is preferably performed using a pipette.
[0059] In the present invention, the self-assembly is preferably carried out under magnetic field induction conditions, and the magnetic field strength induced by the magnetic field is preferably 0.1-0.5T, more preferably greater than 0.1T and less than or equal to 0.5T, and specifically can be 0.2T, 0.3T, 0.4T or 0.5T. In a specific embodiment of the present invention, it is preferred to place the porous 3D scaffold in a well plate, and then drop the magnetic protein solution into the well plate containing the scaffold, and then quickly place the magnet at the bottom of the well plate, and spread the magnetic protein solution on the porous 3D scaffold through magnetic attraction. After 1-2 minutes of forming, remove the magnet to avoid further agglomeration, and stand for 15-20 minutes before absorbing the supernatant, that is, a magnetic particle-protein fiber layer is formed on the surface of the porous 3D scaffold. In the present invention, the amount of magnetic protein solution used affects the size of the obtained magnetic particle-protein fiber assembly. As the volume of the magnetic protein solution decreases, the size of the assembly increases. The amount of magnetic protein solution used can be adjusted according to the required size of the assembly. In a specific embodiment of the present invention, when the diameter of the porous 3D scaffold is 60 to 80 mm and the thickness is 0.1 to 0.3 mm, the volume of the magnetic protein solution used is 0.2 to 1 mL, preferably 0.5 to 1 mL.
[0060] In a specific embodiment of the present invention, the shape and density of the magnetic particle-protein fiber layer can be controlled by adjusting the strength of the magnetic field. The stronger the magnetic field strength, the denser the adsorbed negatively charged silica beads, and the tighter and denser the fiber network formed. Therefore, if a tight and dense fiber layer is prepared, the magnetic field strength can be appropriately increased, such as 0.3-0.5T; when the magnetic force is weak, the adsorbed negatively charged silica beads are less, and the formed fiber network will be looser and have a lower density. Therefore, if a loose fiber layer with large pores is prepared, the magnetic field strength can be reduced, such as 0.1-0.3T; at the same time, a strong magnetic field will also make the fibers present a more vertical and regular orientation, while the fiber orientation will be more random under a weak magnetic field. The present invention forms a magnetic particle-protein fiber layer on the surface of a porous 3D scaffold by self-assembly of negatively charged silica beads and proteins, thereby organically combining magnetic particles with protein fibers, which not only contains magnetic particles that can simulate the bioelectric signals of the bone itself, but also enhances the adsorption capacity of the protein and promotes the adhesion and proliferation of bone cells.
[0061] The present invention also provides a magnetic particle-protein fiber 3D scaffold prepared by the preparation method described in the above scheme, including a porous 3D scaffold and a magnetic particle-protein fiber layer attached to the surface and pore structure of the porous 3D scaffold, wherein the magnetic particle-protein fiber layer is formed by self-assembly of negatively charged oxidized magnetic beads and proteins. In a specific embodiment of the present invention, the sizes of the fibers in the magnetic particle-protein fiber layer formed by different protein types are different, and the diameters are mostly between 50nm and 200nm, and the lengths vary greatly. The short protein fibers may be only a few hundred nanometers, and the long ones can reach several microns or even longer. For example, the fibers formed by magnetic particles and Fg proteins are less than 1μm and as long as 60μm to 80μm.
[0062] The present invention also provides the use of the magnetic particle-protein fiber 3D scaffold described in the above scheme in the preparation of bone repair materials; the present invention has no special requirements for the specific method of the application, and the method familiar to those skilled in the art can be used.
[0063] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] (1) Preparation of grafted hydroxyapatite
[0066] Take 20g of nano-hydroxyapatite powder, add it to 500mL of ethanol, and ultrasonically treat it for 10min to ensure that the nano-hydroxyapatite powder is evenly dispersed in ethanol. Add 10mL of γ-methyl methacrylate silane (MPS) to the solution, and under N2 protection, heat the reaction system to 130°C and continue heating and stirring for 6h. After the grafting reaction is completed, cool the reaction system to room temperature. Wash the product with ethanol and deionized water in turn, and collect the washed product by multiple centrifugation to remove unreacted grafting agent and other impurities. Then freeze-dry the product to obtain grafted hydroxyapatite.
[0067] (2) Preparation of PLPG copolymer
[0068] Weigh 90g PLLA, 5g GA and 5g PDO respectively and put them into a polymerization tube containing 250mL dichloromethane and 5mL Sn(Oct)2 catalyst. Put the polymerization tube into a heating device preheated to 135°C, set the reaction time to 72h, and keep the temperature constant during the polymerization. After the polymerization reaction is completed, take out the polymerization tube, wait for it to cool to room temperature, open the polymerization tube, take out the obtained copolymer, wash it with a solvent, filter it and dry it to obtain a purified PLPG copolymer. The yield of all copolymers is higher than 85%.
[0069] (3) Preparation of porous 3D scaffolds
[0070] Weigh 35g of PLPG copolymer in a beaker, slowly add 200mL of dichloromethane solvent, and stir at the same time until the PLPG copolymer is completely dissolved. Weigh 15g of grafted hydroxyapatite and slowly add it to the PLPG copolymer solution, and use a magnetic stirrer to stir it thoroughly to ensure that the grafted hydroxyapatite is evenly dispersed in the PLPG copolymer solution. After the complex is formed, dry the PLPG / HA complex in a vacuum at 60°C until the weight is constant.
[0071] PLPG / HA composite was used as raw material for 3D printing, and the printing parameters were as follows: printing temperature was 200°C, layer thickness was 0.2mm, printing speed was 45mm / s, filling density was 65%, and printing path was mesh; the printed scaffold was freeze-dried to obtain a porous 3D scaffold with a fiber diameter of 300 microns, a fiber spacing of 300 microns, and an interlayer cross orientation of 90° (referred to as PLPG / HA scaffold), which was then sterilized using 60Co-γ rays with an irradiation dose of 25kGy. The porous 3D scaffold obtained according to the above method is as follows Figure 1 Mechanical property tests show that the compressive strength of the porous 3D scaffold prepared by the present invention reaches 50Mpa, which has a similar supporting force to that of the main bone.
[0072] Example 2
[0073] (1) Preparation of Fe3O4@SiO2 by sol-gel reaction
[0074] The specific method is as follows: add ammonium hydroxide to the mixed liquid of ethanol and deionized water to adjust the pH to 10. Add 150mg Fe3O4 NPs under ultrasonic treatment. Dissolve 80μL of TEOS in 1mL of ethanol and then add dropwise to the reaction system. Stir the reaction at room temperature for 12h. Wash with ethanol and deionized water three times respectively to obtain Fe3O4@SiO2 nanoparticles.
[0075] (2) Carboxyl functionalization of Fe3O4@SiO2
[0076] Carboxyl functionalization is performed on silica-coated magnetic particles to improve the dispersibility of magnetic nanoparticles and give them a negatively charged functional surface.
[0077] The specific method is as follows: Fe3O4@SiO2 nanoparticles are dispersed in anhydrous ethanol, ultrasonically dispersed for 10 minutes, 3-methyl methacrylate (MAA) monomer is added, the mass ratio is Fe3O4@SiO2:MAA=1:3, and stirred at 80°C for 2 hours to promote the condensation reaction between MAA and the siloxane groups on the surface of SiO2. After the reaction is completed, it is repeatedly washed with ethanol or water, and the functionalized SiO2-Fe3O4-PMAA nanoparticles are collected by centrifugation. The collected nanoparticles are vacuum dried at 60°C for 2 hours to obtain the final product, which is the negatively charged silicon oxide magnetic beads of the present invention.
[0078] (3) Preparation of protein solution
[0079] Fibronectin (Fn) solution: Weigh 5 μg of fibronectin (Fn) into a sterile centrifuge tube, and use a pipette to add 1 mL of PBS solution into the centrifuge tube. Gently flip the centrifuge tube until the protein is completely dissolved to obtain a 0.005 mg / mL Fn solution.
[0080] Laminin solution: Weigh 0.01 mg of laminin into a sterile centrifuge tube, and use a pipette to add 1 mL of PBS solution into the centrifuge tube. Gently flip the centrifuge tube until the protein is completely dissolved to obtain a laminin solution with a concentration of 0.01 mg / mL.
[0081] Type I collagen (COL-1) solution: Weigh 0.01 mg of type I collagen into a sterile centrifuge tube, and use a pipette to add 1 mL of PBS solution into the centrifuge tube. Gently flip the centrifuge tube until the protein is completely dissolved to obtain a COL-1 solution with a concentration of 0.01 mg / mL.
[0082] Bovine serum albumin (BSA) solution: Weigh 0.1 mg of bovine serum albumin into a sterile centrifuge tube, and use a pipette to add 1 mL of PBS solution into the centrifuge tube. Gently flip the centrifuge tube until the protein is completely dissolved to obtain a BSA solution with a concentration of 0.1 mg / mL.
[0083] Bovine fibrinogen (Fg) solution: Accurately weigh 1 mg of bovine fibrinogen (Fg) and place it in a sterile centrifuge tube. Use a pipette to add 1 mL of PBS solution to the centrifuge tube. Gently flip the centrifuge tube until the protein is completely dissolved to obtain a 1 mg / mL Fg solution.
[0084] (4) Preparation of magnetic particle-protein fiber assemblies
[0085] Add 0.1 mg of negatively charged silica beads that have been fully ultrasonicated to 1 mL of protein solution and incubate at 4°C for 10 minutes, gently turning upside down every 2 minutes. After the clusters are formed, place the centrifuge tube on a magnetic stand for 2-10 minutes of magnetic absorption. After resuspending with a pipette, drop 1 mL of the magnetic protein solution into the well plate containing the cell slide or the well plate containing the 3D porous scaffold. Quickly place a small magnet with a magnetic field strength of 0.3 T at the bottom of the well plate, and spread it on the cell slide or scaffold through magnetic absorption. After about 1 minute of formation, remove the magnet to avoid further agglomeration, let it stand for 20 minutes, and remove the supernatant. The magnetic particle-protein fiber assembly formed on the cell slide is a 2D planar bionic static fiber layer, and the 3D three-dimensional bionic static fiber layer is formed on the scaffold.
[0086] Figure 2 Microscope images of 2D planar biomimetic static fiber layers formed by self-assembly of different protein solutions and negatively charged silica magnetic beads. Figure 2 It can be seen that as time changes, negatively charged silica beads and proteins self-assemble to form aggregates and gradually form fibrous assemblies. In addition, the pore morphology of the fibrous structures formed by self-assembly of different proteins in this system is different.
[0087] The same experiment was performed by changing the drop volume of the magnetic protein solution, wherein the protein was BSA and the volumes of the magnetic protein solution were 1 mL, 0.5 mL and 0.25 mL, respectively. Figure 3 Microscope images of 2D biomimetic static fiber layers formed by magnetic protein solutions with different volumes. Figure 3 It can be seen that after changing the volume of the magnetic protein solution, the morphology of the assembly does not change much, but the size of the assembly will change. As the solution volume decreases, the size of the assembly increases.
[0088] Example 3 Biocompatibility and cell proliferation studies
[0089] (1) MC3T3-E1 cells were used as the research object and cultured at 37°C in a humidified environment incubator with 5% carbon dioxide. The cell culture medium contained 89 vol% MEM-ɑ, 10 vol% fetal bovine serum (FBS) solution and 1 vol% penicillin / streptomycin.
[0090] MC3T3-E1 cells were inoculated on the magnetic particle-protein fiber assembly (2D planar fiber layer prepared in Example 2) formed by combining different proteins with negatively charged silica magnetic beads, and incubated for 24 h and 48 h, respectively. CCK-8 working solution was added and incubated for 1.5 h, and the OD value was quantified at 450 nm absorbance using a multifunctional microplate reader, and the cell activity was calculated based on the OD value, with PBS as the control group.
[0091] Figure 4 The results of the cell activity test of MC3T3-E1 cells in different magnetic particle-protein fiber assemblies; Figure 4 The results show that the cell survival rates are all above 90%, indicating that the assembly can well support cell proliferation; there are certain differences in the effects of different magnetic particle-protein fiber assemblies on MC3T3-E1 cells. For example, the assembly formed by laminin (Laminin)-negatively charged silica beads has a cell survival rate of up to 140%, indicating that the assembly can significantly promote cell growth and proliferation.
[0092] (2) Following the same method as in (1), MC3T3-E1 cells were inoculated on the porous 3D scaffolds before and after modification with magnetic particle-protein fiber coating and incubated for 24 h and 48 h, respectively. A pre-prepared PBS mixed solution of 2 μM calcein AM and 8 μM propidium iodide PI was added and stained at 37°C for 30 min. Fluorescence staining was observed and captured by fluorescence microscopy (LEICA), and live-dead staining analysis was performed using Image J software to determine cell proliferation and the cell compatibility of the material.
[0093] Figure 5 The live and dead cell staining results of MC3T3-E1 cells after 48 hours of culture on the porous 3D scaffolds before and after modification. The scaffold is the porous 3D scaffold before modification, the coated scaffold is the porous 3D scaffold after modification, and the protein used is type I collagen. Figure 5As can be seen from the results, almost all cells on the porous 3D scaffolds before and after modification are green (live cells), with only a few red (dead cells). This shows that the scaffold material of the present invention has good biocompatibility, and the scaffold material itself has no obvious toxic effect on cells, and does not cause a large number of cell deaths; the modified porous 3D scaffolds show a richer distribution of green live cells, indicating that the porous 3D scaffolds modified with the magnetic particle-protein fiber layer have better cell adhesion and growth, and the 3D structure and microenvironment conditions of the scaffold can provide cells with a good growth space and nutrient supply.
[0094] Example 4 Study on cell adhesion characteristics
[0095] The cell adhesion was detected by cell immunofluorescence staining. The specific experimental method is as follows:
[0096] MC3T3-E1 cells were inoculated on 2D planar fiber layers formed by combining different proteins with negatively charged silica beads or on modified porous 3D scaffolds and cultured for 24h and 48h, respectively. Cells were fixed with 4% paraformaldehyde for 30min, permeabilized with 0.1% TritonX-100 for 10min, and blocked with PBS containing 1% BSA for 30min to reduce nonspecific binding. Cells were incubated with Vinculin antibody and integrinβ antibody at 4°C overnight, and the cells were washed with PBS to remove unbound antibodies. F-actin antibody was incubated at room temperature for 30min for cytoskeleton staining. Finally, 5μg / mL DAPI was used for nucleus staining. Confocal fluorescence microscopy was used to observe cell adhesion morphology. Three parallel samples were set up for each experiment, and PBS was used as the control group.
[0097] Figure 6 The immunofluorescence staining and semi-quantitative analysis results of MC3T3-E1 cells cultured in 2D planar bionic static fiber layers for 48 hours; Figure 6 It can be seen that compared with the control group, the protein coating group showed obvious cytoplasmic diffusion, showing clearly visible cytofilaments and pseudopodia, especially in the COL-1 group and the Fg group. In addition, the protein coating can also promote cell attachment to the scaffold through integrin receptors. These characteristics indicate that the protein-coated scaffold can promote cell proliferation and adhesion.
[0098] Figure 7 The immunofluorescence staining results of MC3T3-E1 cells cultured on the porous 3D scaffolds before and after modification for 48 hours are shown in Figure 1. The scaffold is the porous 3D scaffold before modification, the coated scaffold is the porous 3D scaffold after modification, and the protein used is Fg. Figure 7It can be seen that the cells present a regular morphology on the scaffold with clear cell outlines. Compared with the simple scaffold group, the cells in the coated scaffold group are more closely connected, forming a continuous cell layer. Vinculin protein is clearly developed around the cells, providing a dynamic anchoring protein for connecting the cytoskeleton and the extracellular matrix (ECM).
[0099] Example 5
[0100] The density of the fiber layer was reduced to prepare a low-density coated stent. The specific preparation method was the same as that in Example 2, except that the magnetic field intensity was changed to 0.1 T and the protein used was type I collagen.
[0101] According to the method in Example 3(2), the biocompatibility and cell proliferation of the low-density coated stent were studied to observe the effect of the low-density coated stent on cell behavior. Figure 8 The live and dead cell staining results of MC3T3-E1 cells cultured on low-density coated scaffolds for 48 hours. Figure 8 It can be seen that when the density of the protein coating is low, the adhesion and diffusion ability of the cells decreases, the cell morphology is more rounded, and the cells fail to fully stretch. This shows that the density of the fiber layer affects the effective contact between the cells and the ECM, and affects the normal attachment and growth of the cells. In the specific implementation of the present invention, the density of the fiber layer can be regulated by the magnetic field strength according to actual needs.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a magnetic particle-protein fiber 3D scaffold, characterized in that: The following steps are involved: The polylactic acid, glycolide, cyclohexanone, a catalyst and a solvent are mixed to carry out a polymerization reaction to obtain a copolymer; The copolymer and grafted hydroxyapatite are mixed to obtain a copolymer-grafted hydroxyapatite composite; the grafted hydroxyapatite comprises hydroxyapatite and a silane coupling agent grafted on the surface of the hydroxyapatite; 3D printing the copolymer-grafted hydroxyapatite composite to obtain a porous 3D scaffold; The magnetic protein solution is dripped onto the porous 3D scaffold for self-assembly to obtain the magnetic particle-protein fiber 3D scaffold; the magnetic protein solution includes a protein solution and negatively charged silica magnetic beads dispersed in the protein solution; the negatively charged silica magnetic beads include Fe3O4 nanoparticles, a silica layer coated on the surface of the Fe3O4 nanoparticles, and a carboxyl functional group modified on the silica layer.
2. The preparation method according to claim 1, characterized in that: The mass ratio of polylactic acid, glycolide and cyclohexanone is 50-90:5-25:5-25; The weight average molecular weight of the polylactic acid is 50,000 to 150,000; The catalyst comprises one or more of organic tin and organic sulfonic acid; the mass of the catalyst is 0.05-5% of the total mass of the polylactic acid, glycolide and cyclohexanone.
3. The preparation method according to claim 1 or 2, characterized in that: The polymerization reaction temperature is 130-145° C., and the reaction time is 70-84 hours.
4. The preparation method according to claim 1, characterized in that: The preparation method of the grafted hydroxyapatite comprises: mixing hydroxyapatite, a silane coupling agent and an alcohol solvent for grafting reaction to obtain the grafted hydroxyapatite; the grafting reaction temperature is 120-140° C., and the reaction time is 5-7 hours.
5. The preparation method according to claim 1 or 4, characterized in that: The silane coupling agent includes one or more of γ-methyl methacrylate silane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and 3-aminopropyltriethoxysilane; The molar ratio of the hydroxyl groups on the surface of the hydroxyapatite to the alkoxy groups in the silane coupling agent is 1:1-2.
6. The preparation method according to claim 1, characterized in that: The method for mixing the copolymer and the grafted hydroxyapatite comprises: dissolving the copolymer in an organic solvent to obtain a copolymer solution; mixing the grafted hydroxyapatite and the copolymer solution, and drying the obtained mixed liquid to obtain the copolymer-grafted hydroxyapatite composite; The mass ratio of the copolymer to the grafted hydroxyapatite is 7-9:1-3.
7. The preparation method according to claim 1, characterized in that: The 3D printing conditions include: a printing temperature of 180 to 220°C, a layer thickness of 0.1 to 0.3 mm, a printing speed of 20 to 60 mm / s, a filling density of 20 to 80%, and a linear or mesh printing path; The porous 3D scaffold has a porosity of 60-90% and a pore size of 100-500 μm.
8. The preparation method according to claim 1, characterized in that: The self-assembly is carried out under magnetic field induction conditions, and the magnetic field intensity of the magnetic field induction is 0.1-0.5T.
9. The magnetic particle-protein fiber 3D scaffold prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises a porous 3D support and a magnetic particle-protein fiber layer attached to the surface of the porous 3D support, wherein the magnetic particle-protein fiber layer is formed by self-assembly of negatively charged oxidized magnetic beads and proteins.
10. Use of the magnetic particle-protein fiber 3D scaffold according to claim 9 in the preparation of bone repair materials.